MODERN IMPERATIVE FOR THE FORMATION AND DEVELOPMENT OF THE COMPANY'S PERSONNEL MANAGEMENT SYSTEM BASED ON DETERMINING THE IMPACT OF FACTORS - Kokenova A. T.,; Kupesheva A. K.,; Mashirova T. N.,; Statsenko O. A.,; Zhabayeva B. O., (Scientific Journal of Pedagogy and Economics, 2021)
. Our country has accumulated considerable experience in the study of quality management problems, and there is also a large number of works on the problems of personnel management. However, very few attempts were made to apply a systematic approach to the problem under study, the analysis of personnel management as the most important factor in quality assurance. Currently, management sciences lack fundamental research that provides a holistic view of quality management. The purpose of the study is to develop the key principles of the Kazakhstan model of personnel management that are adequate to modern requirements for product quality and take into account the specifics of Kazakhstan on the basis of understanding domestic and foreign experience. The theoretical and methodological basis of the study was the conceptual provisions on the unity of man and the social environment; on the individual as a subject of joint activity and personal development; on the determinism of the functioning and development of the individual by the system of national value priorities, spiritual and material needs. The scientific article proposes measures to improve personnel management, concerning: reorientation of the worldview of modern Kazakh managers on the quality of products, works and services; creation of a favorable business social and managerial environment for their respective activities; orientation of the main functions of personnel management to the general model of quality management; formation of an effective mechanism for involving employees in the quality management process; motivation of personnel activities to ensure quality